Invisibility as a structural determinant: Mortality outcomes of Asians and Pacific Islanders experiencing homelessness - Chang, Jamie Suki; Saxton, Katherine; Bright, Georgia; Ryan, Maya S.; Lai, E. Francis; Jorden, Michelle A.; Gutierrez, Andy (Frontiers in Public Health, 2023)
Introduction Asians and Pacific Islanders (APIs) who are experiencing homelessness are situated in a social intersection that has rendered them unrecognized and therefore vulnerable. There has been increasing attention to racial disparities in homelessness, but research into API homelessness is exceedingly rare, despite rapidly growing populations. The purpose of this study is to examine the causes of death among APIs who died while homeless in Santa Clara County (SCC) and compare these causes to other racial groups. Materials and methods We report on data obtained from the SCC Medical Examiner-Coroner's Office on unhoused people's deaths that occurred between 2011 and 2021 (n = 1,394), including data on deaths of APIs experiencing homelessness (n = 87). Results APIs comprised 6.2% of total deaths of unhoused people. APIs died less often of causes related to drug/alcohol use than all other racial groups (24.1, compared to 39.3%), and there was a trend toward more API deaths from injuries or illnesses. When APIs were disaggregated into sub-groups (East/Southeast Asian, South Asian, Pacific Islander), there were notable mortality differences in cause of death, age, and sex. Discussion We argue that invisibility is a structural determinant of health that homeless APIs face. Though relatively small in numbers, APIs who are invisible may experience increased social isolation and, subsequently, specific increased mortality risks. To understand the health outcomes of unhoused APIs, it is essential that researchers and policymakers recognize API homelessness and gather and report disaggregated races and ethnicities.